2011
DOI: 10.1007/s00439-011-1101-y
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics DNA methylation in the core ataxin-2 gene promoter: novel physiological and pathological implications

Abstract: Pathogenic CAG (cytosine-adenine-guanine) expansions beyond certain thresholds in the ataxin-2 (ATXN2) gene cause spinocerebellar ataxia type 2 (SCA2) and were shown to contribute to Parkinson disease, amyotrophic lateral sclerosis and frontotemporal lobar degeneration. Regulation of ATXN2 gene expression and the function of the protein product are not known. SCA2 exhibits an inverse correlation between the size of the CAG repeat and the age at disease onset. However, a wide range of age at onset are typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Another gene involved in a form of ataxia, the spinocerebellar ataxia type 2 (SCA2), is the ataxin-2 ( ATXN2 ) gene; the CAG repeat in the mutant gene only partially accounts for the wide range of observed age of onset. It was demonstrated that DNA methylation might regulate the expression of the mutant gene modulating the onset and the severity of the disease [ 76 ]. Since this gene is also involved in Parkinson ' s disease, amyotrophic lateral sclerosis and frontotemporal lobar degeneration, it is highly probable that at least a part of the epigenetic contribution hypothesized for these diseases can be attributable to the methylation pattern of the ATXN2 gene.…”
Section: Dna Methylation and Neurodegenerationmentioning
confidence: 99%
“…Another gene involved in a form of ataxia, the spinocerebellar ataxia type 2 (SCA2), is the ataxin-2 ( ATXN2 ) gene; the CAG repeat in the mutant gene only partially accounts for the wide range of observed age of onset. It was demonstrated that DNA methylation might regulate the expression of the mutant gene modulating the onset and the severity of the disease [ 76 ]. Since this gene is also involved in Parkinson ' s disease, amyotrophic lateral sclerosis and frontotemporal lobar degeneration, it is highly probable that at least a part of the epigenetic contribution hypothesized for these diseases can be attributable to the methylation pattern of the ATXN2 gene.…”
Section: Dna Methylation and Neurodegenerationmentioning
confidence: 99%
“…Mutated ataxin-2 protein has been shown to alter the activity of calcium channels in Purkinje cells of brain and thus causing their death via apoptosis [13]. Moreover, hypermethylation of the promoter region of the ataxin-2 gene was also found to be associated with the pathogenic expansion of CAG repeats and the onset of SCA2 [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The ATXN2 promoter contains a CpG island rich segment without a TATA box. Both hyper-and hypomethylation states are found in the ATXN2 promoter in SCA2 patients [69,70]. In SCA1, local DNA methylation patterns have been detected at ATXN1 locus.…”
Section: Alteration Of Methylation In Scasmentioning
confidence: 93%
“…Confounding by genetics or shared mother-child environmental factors is a particular concern that should be addressed. For example, paternal alcohol consumption could be employed as a 'negative control' that will share the same confounding structure as maternal alcohol consumption but cannot plausibly affect offspring DNA methylation through a direct causal intrauterine mechanism [70]. Techniques such as two-step Mendelian randomization [71] could also be applied to explore the causal effect of prenatal alcohol exposure on DNA methylation and the causal effect of DNA methylation on offspring outcomes.…”
Section: Discussionmentioning
confidence: 99%